Engineering Assessment of Earthquake Resistant Building Code Based on Seismic Load Responses - Dwi Yanto; Tavio; Jusuf, Andrew Hartanto (Science and Technology Research Centre Universitas PGRI Semarang, 2026)
Earthquake-resistant building design is fundamentally aimed at safeguarding life safety while controlling structural damage and preserving post-earthquake functionality under uncertain seismic actions. Although contemporary seismic codes provide detailed procedures for estimating earthquake-induced loads, differences in seismic hazard representation, force distribution rules, and deformation assumptions can lead to considerable variation in predicted structural response. This study presents a comprehensive engineering assessment of earthquake-resistant building codes based on seismic load responses in reinforced concrete moment-resisting frame structures. An integrated analytical framework combining elastic seismic analysis and nonlinear static performance evaluation is adopted to examine global force demand, displacement behavior, stiffness degradation, and post-yield response. Particular attention is given to the interaction between force-based seismic demand indicators, such as base shear and story forces, and deformation-based performance measures, including interstory drift and performance point characteristics. By systematically evaluating structural response across elastic and inelastic stages, the study demonstrates that reliance on elastic force demand alone is insufficient for capturing true seismic performance. The results emphasize the importance of performance-oriented assessment in enhancing the reliability, consistency, and resilience of earthquake-resistant building design.